Medieval anchorites in their communities - Gunn, Cate; Herbert McAvoy, Liz (Studies in the history of medieval religion, 2017)
Much of the research into medieval anchoritism to date has focused primarily on its liminal and elite status within the socio-religious cultures of its day. The anchorite has long been depicted as both solitary and alone, almost entirely removed from community and living a life of permanent withdrawal and isolation: in effect dead to the world. The essays in this volume, stemming from a variety of cross-disciplinary approaches and methodologies, lay down a challenge to this position, breaking new ground in their presentation of the medieval anchorite and other types of enclosed solitary as playing a central role within the devotional life of a whole range of complex and multifaceted communities: ones that were simultaneously synchronic and diachronic, physical and metaphysical, religious, secular, textual - and gendered. It therefore offers its readers a new way of understanding the operations of the solitary life in the Middle Ages and its interdependence with a whole array of communities, ultimately adding to our knowledge of how spiritual "aloneness" could be pursued ardently, even in the midst of communal interaction